Fatigue damage behavior in carbon fiber polymer composites under biaxial loading. (1st October 2019) - Skinner, Travis; Datta, Siddhant; Chattopadhyay, Aditi; Hall, Asha
Abstract: An investigation into the damage accumulation and propagation behavior in carbon fiber reinforced polymer (CFRP) composites under complex in-phase biaxial fatigue loading has been conducted. The goal is to capture early stage damage and obtain an improved understanding of damage propagation and associated degradation in material properties. Both cross ply and quasi isotropic laminate configurations have been studied and the tests were conducted under constant amplitude in-phase biaxial loading. An optimization technique was used to design the cruciform specimens for each stacking sequence. To understand the propagation of damage from the micro-to the macroscale, the fractured surfaces were analyzed, during various stages of fatigue, using electron microscope assisted fractography and a high-resolution camera. Material property degradation was determined by measuring the change in specimen stiffness to analyze the progression of fatigue damage and is correlated to the micro- and macroscale damage mechanisms and the biaxial fatigue loading parameters. The results provide insight into the initiation and propagation of damage mechanisms in CFRP composites which is essential to understanding the fatigue behavior of composite materials under complex multiaxial loadings.